Asymmetric biodegradation of the nerve agents Sarin and VX by human dUTPase: chemometrics, molecular docking and hybrid QM/MM calculations. Issue 8 (24th May 2019) - de Castro, Alexandre A.; Soares, Flávia Villela; Pereira, Ander Francisco; Silva, Telles Cardoso; Silva, Daniela Rodrigues; Mancini, Daiana Teixeira; Caetano, Melissa Soares; da Cunha, Elaine F. F.; Ramalho, Teodorico C.
Abstract: Organophosphorus compounds (OP) nerve agents are among the most toxic chemical substances known. Their toxicity is due to their ability to bind to acetylcholinesterase. Currently, some enzymes, such as phosphotriesterase, human serum paraoxonase 1 and diisopropyl fluorophosphatase, capable of degrading OP, have been characterized. Regarding the importance of bioremediation methods for detoxication of OP, this work aims to study the interaction modes between the human human deoxyuridine triphosphate nucleotidohydrolase (dUTPase) and Sarin and VX, considering their Rp and Sp enantiomers, to evaluate the asymmetric catalysis of those compounds. In previous work, this enzyme has shown good potential to degrade phosphotriesters, and based on this characteristic, we have applied the human dUTPase to the OP degradation. Molecular docking, chemometrics and mixed quantum and molecular mechanics calculations have been employed, showing a good interaction between dUTPase and OP. Two possible reaction mechanisms were tested, and according to our theoretical results, the catalytic degradation of OP by dUTPase can take place via both mechanisms, beyond being stereoselective, that is, dUTPase cleaves one enantiomer preferentially in relation to other. Chemometric techniques provided excellent assistance for performing this theoretical investigation. The dUTPase study shows importance by the fact of it being a human enzyme. Communicated by Ramaswamy H. Sarma